Allorecognition of human neural stem cells by peripheral blood lymphocytes despite low expression of MHC molecules: role of TGF-β in modulating proliferation - Ubiali, Federica; Nava, Sara; Nessi, Valeria; Frigerio, Simona; Parati, Eugenio; Bernasconi, Pia; Mantegazza, Renato; Baggi, Fulvio (International immunology, 2007)
Neural stem cells (NSCs) transplantation has been proposed as a means of restoring damaged brain tissue, a possibility rendered more likely by reports of low NSCs immunogenicity in various experimental models because of low expression of MHC class I and II as well as co-stimulatory molecules. We investigated the immunogenicity of a human NSC line grown in normal culture conditions and in the presence of pro-inflammatory cytokines IFN-γ and tumor necrosis factor alpha by one-way mixed lymphocyte reaction (MLR) experiments with peripheral blood lymphocytes from eight HLA-incompatible donors. NSCs stimulated lymphocyte proliferation in almost all donors tested, with stimulation indices in the range of the low-end distribution curve of MLR between donors. The healthy subject that gave negative MLR results was the best compatible donor with respect to NSC haplotype. Since we observed low MLR responses overall, we studied if NSCs might exert any immunomodulatory activity. We detected transcription and release of the immunomodulatory molecule transforming growth factor beta (TGF-β)-1; moreover, the addition of TGF-β1 in MLR experiments down-regulated proliferative responses. To further confirm the immunological potential of human NSCs, we studied xenogeneic recognition of NSCs by immunocompetent cells derived from C57BL/6 mice, showing that NSCs can elicit an allo(xeno) response ex vivo. Our data indicate that NSCs have low but not negligible immunogenic potential that is sufficient to activate peripheral lymphocytes. Secretion of TGF-β1 might balance the immunogenicity of NSCs. Nevertheless, the possibility that allo-NSCs grafting might induce in the long term an immune activation, thus vanishing their therapeutical effect, should not be overlooked and deserves further investigation.